Lichen planus and it’s association with diabetes mellitus - Adhikari, Sabina; Anupama Karki (Asian Journal of Medical Sciences, 2022)
Background: Lichen planus(LP) is a unique common inflammatory disorder that is clinically characterized by violaceous pruritic flat polygonal papules or plaques. Recently, an association between LP and diabetes mellitus has been viewed with greater interest.Several studies done in assessing the association between these show conflicting results. Aims and Objectives: The aim of this study was to find an association between LP and diabetes mellitus. Materials and Methods: A cross-sectional comparative study was conducted in the Outpatient Department (OPD) of Dermatology, Bir Hospital. Any patient presenting at dermatology OPD above 16 years of age with LP were taken as cases. Age- and gender-matched patients with skin disease other than LP were taken as controls. The test was done by collecting 2ml of blood and serum HbA1c level was assessed allowing the blood to stand in a cuvette for 5 min inside the Erba Mannheim XL-300 analyzer to interact with DS5 reagent. The result was interpreted as per the calibration in the printed chromatogram. Results: Male preponderance with a male: female ratio of 1.08:1 was found in this study. The mean age of onset of LP was earlier in male 40.11 years than in female 44.66 years.Likewise, hypertrophic(30%) followed by eruptive(27.5%) wasthe most common variants of LP found in this study. Diabetes was more common in males(75%) with LP than in females(25%) with LP. Patients having longer duration of LP were more commonly associated with diabetes mellitus. Among clinical variants of LP, diabetes was associated more with eruptive variant followed by classic and hypertrophic variants. The prevalence of diabetes was higher in case(16%) than in control(4%),P=0.046. Conclusion: This study showed an association of LP with diabetes mellitus, the association being statistically significant(P=0.046). It, therefore, is desirable to do HbA1c level screening in patients with LP for timely detection of diabetes mellitus.